Histone acetylation and the role of histone deacetylases in normal cyclic endometrium - Palak Gujral; Vishakha Mahajan; Abbey C. Lissaman; Anna P. Ponnampalam (BMC, 2020)
Abstract Histone acetylation is a critical epigenetic modification that changes chromatin architecture and regulates gene expression by opening or closing the chromatin structure. It plays an essential role in cell cycle progression and differentiation. The human endometrium goes through cycles of regeneration, proliferation, differentiation, and degradation each month; each phase requiring strict epigenetic regulation for the proper functioning of the endometrium. Aberrant histone acetylation and alterations in levels of two acetylation modulators - histone acetylases (HATs) and histone deacetylases (HDACs) - have been associated with endometrial pathologies such as endometrial cancer, implantation failures, and endometriosis. Thus, histone acetylation is likely to have an essential role in the regulation of endometrial remodelling throughout the menstrual cycle.